Beta-Hydroxybutyrate, Friend or Foe for Stressed Hearts - Chu, Yuxin; Zhang, Cheng; Xie, Min (Frontiers in Aging, 2021)
One of the characteristics of the failing human heart is a significant alteration in its energy metabolism. Recently, the ketone body, β-hydroxybutyrate (β-OHB), has been implicated in the failing heart’s energy metabolism as an alternative “fuel source”. The utilization of β-OHB increases in the failing heart, and this “fuel switch” has been demonstrated to be an adaptive response to stress during heart failure progression in both diabetic and non-diabetic patients. In addition to serving as an alternative “fuel”, β-OHB is a signaling molecule that acts as an endogenous histone deacetylase (HDAC) inhibitor. It can increase histone acetylation or lysine acetylation of other signaling molecules. β-OHB has been shown to decrease the production of reactive oxygen species and activate autophagy. Moreover, β-OHB works as an NLR family pyrin domain-containing protein 3 (Nlrp3) inflammasome inhibitor and reduces Nlrp3-mediated inflammatory responses. There are other transcriptional or post-translational regulations of various genes by β-OHB that have been reported. Increased levels of β-OHB before ischemia/reperfusion injury in rodents reduce infarct size, likely through its signaling function in addition to providing energy. Sodium-glucose co-transporter-2 (SGLT2) inhibitors have been shown to exert strong beneficial effects on the cardiovascular system. They are also capable of increasing the production of β-OHB, which may partially explain their clinical efficacy. Despite all of the beneficial effects of β-OHB, studies show detrimental effects of long-term exposure to β-OHB. Furthermore, not all means of increasing β-OHB are as effective in treating heart failure. Thus, it is still not clear what is the best timing and therapeutic agent to deliver β-OHB to treat heart disease. In this review, we focus on the crucial role of ketone bodies, particularly β-OHB, as an energy source as well as a signaling molecule for stressed hearts and its therapeutic potential for cardiovascular diseases.